Stichwortbeitrag "awareness set", "cause-related marketing, "cobranding", "consideration set", "corporate social responsibility", "lead user", "Marktsegmentierung", "Positionierung", "Präferenzbildung", "processed set" - Koschate-Fischer, Nicole; Liebetrau, Jennifer; Wolframm, Christiane (Dorsch-Lexikon der Psychologie, 2019)

Toward Developing a Valenced Model of Fit in Cause-related Marketing: An Abstract - Liebetrau, Jennifer; Basil, Debra Z. (Enlightened Marketing in Challenging Times. Proceedings of the 2019 AMS World Marketing Congress (WMC), 2020)
This research tests a valenced model of fit for cause-related marketing (CRM) partnerships developed by Liebetrau et al. (2018). Liebetrau et al.’s (2018) model proposes nine specific categories of fit, particularly drawing from Zdravkovic et al. (2010) and Basil and Basil (2003). Specifically, the model examines two key factors: valence and commonality. Valence refers to whether the company and the cause are apparently working toward a unified purpose or cross-purposes outside of the partnership. Commonality refers to whether the company and cause appear to have something in common. Crossing these factors develops a two-dimensional space upon which three general types of CRM fit (positive, neutral, and negative) are placed and within these general types, nine different sub-types of CRM fit are placed. An on-line, scenario-based experiment was conducted to assess the proposed model. Participants were sourced from Amazon’s Mechanical Turk, resulting in 544 usable responses. Model fit, attitude, and purchase intention toward the general fit types of CRM partnerships were assessed. Fit was shown to be a multi-faceted concept, yet individuals see differences in the types of fit relatively consistently. Positive fit was most consistently categorized, rated on commonality and valence, and had the most favorable attitudes and purchase intentions. The high CRM attitude and purchase intention ratings for the various forms of positive fit (natural fit, mission, and function fit) suggest that if the supported cause or charity is directly related to a company’s business practice, purpose, written statement, or products, consumers recognize and reward that. Among the negative fit sub-types, the form of negative fit impacted consumer response. Prevention fit, which occurs when a company attempts to alleviate the harm they cause, has potential to evoke favorable attitudes and higher purchase intentions. Prevention fit can be used by companies to communicate a behavior change, whereby the company moves away from creating a harmful effect on the cause to actively addressing and changing its behavior. Other forms of negative fit (e.g. complicity and redresser) may be somewhat confusing to consumers and therefore risky to use. Marketers are advised to exercise caution when contemplating a negative fit CRM alliance. Model revisions were proposed based on study results. These should be tested in further empirical research. In summary, it was demonstrated that consumers consistently see discernable differences between CRM partnerships based on the nature of the fit between company or brand and charity, and the fit distinctions proposed by the model are a useful means of understanding these differences.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Alliance; Cause-related marketing; Fit; Partnership